Influence of plane wave cut-off on structural and electronic properties in Sn-BEA and Ti-BEA zeolite water molecule interaction - Kulkarni, Bhakti S.; Krishnamurty, Sailaja; Pal, Sourav (Chemical Physics Letters, 2010)
Periodic systems are best described by the pseudo-potential methods. However, the accuracy of its description depends on the cut-off of plane wave basis. This is much more critical in the case of weak interactions, where a clear understanding on the influence of plane wave cut-off on the structural and electronic properties is not readily available in the literature. In the present work, we have taken a metal substituted beta zeolite-H2O complex for understanding this objective. Our studies show that while a lower cut-off of 500 eV is sufficient for the convergence of the structural parameters, description of energy-dependent properties necessitates a high cut-off value. (C) 2009 Elsevier B.V. All rights reserved.